2000
DOI: 10.1093/ajcn/72.4.937
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and dietary intakes in adult celiac disease patients consuming a strict gluten-free diet

Abstract: Background: Celiac disease responds to dietary gluten withdrawal, but data on the long-term effects of gluten-free diets are discordant. Objective: Our aim was to evaluate the nutritional status and body composition of adult celiac disease patients consuming a gluten-free diet who were in clinical, biochemical, and histologic remission. Design: We studied 71 patients (51 women and 20 men; mean age: 27 y; range: 17-58 y) and 142 healthy control subjects matched by sex and age. The subjects' height, weight, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
119
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 12 publications
(14 reference statements)
15
119
1
9
Order By: Relevance
“…Of greater concern is that over one-third of patients are exceeding the recommended percentage of energy from fat. In contrast to findings in previous studies (Kemppainen et al, 1995;Bardella et al, 2000;Capristo et al, 2000) our results showed that patients with CD are actually having a lower average intake of fat than the general population, and get a smaller proportion of total energy from fat. Only one study has found similar findings and this was only in females (Bjorkman et al, 1985).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Of greater concern is that over one-third of patients are exceeding the recommended percentage of energy from fat. In contrast to findings in previous studies (Kemppainen et al, 1995;Bardella et al, 2000;Capristo et al, 2000) our results showed that patients with CD are actually having a lower average intake of fat than the general population, and get a smaller proportion of total energy from fat. Only one study has found similar findings and this was only in females (Bjorkman et al, 1985).…”
Section: Discussioncontrasting
confidence: 99%
“…Bjorkman et al (1985) and Bardella et al (2000) found that the GFD resulted in a significant decrease in mean energy intake and significantly lower total daily intake of energy than controls, whereas Kemppainen et al (1995) found intakes of energy were significantly greater in patients with CD compared to the controls (Po0.05). Collins et al (1986) found that 24% patients had a lower energy than the estimated average requirements (EARs).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, little information is available on the nutritional composition of these GF products. Composition data useful to evaluate the adequacy of nutrient intake of coeliac patients, on which the debate is still open (6)(7)(8)(9) , are therefore strongly needed. In the present work, we built a database of composition of a number of foods representing the main sources of intake of GF products in the Italian diet.…”
mentioning
confidence: 99%